5z-10z=7z

Simple and best practice solution for 5z-10z=7z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-10z=7z equation:


Simplifying
5z + -10z = 7z

Combine like terms: 5z + -10z = -5z
-5z = 7z

Solving
-5z = 7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7z' to each side of the equation.
-5z + -7z = 7z + -7z

Combine like terms: -5z + -7z = -12z
-12z = 7z + -7z

Combine like terms: 7z + -7z = 0
-12z = 0

Divide each side by '-12'.
z = 0

Simplifying
z = 0

See similar equations:

| .3(12+x)=.6+.35x | | 6+p+7p=3p+6+5p | | s+2+2s-10=180 | | 10=30x+10 | | -6-5j+1=-3j+9 | | 12x-6=3(x+9) | | 13(x-2)=8x-6 | | 123456790*23456789+1234567890= | | 10=-30x+10 | | (w)=0 | | .25(12+x)=.6+.35x | | 9p^2-12p=0 | | (w)=1 | | (w)=-1 | | -9n^2-9=315 | | 5+6x+25=180 | | (w)=-2 | | 8-10p=88 | | 4c-10=-9+3c | | (7y+2)(y-5)= | | 8x(8+6x)=20 | | .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 |

Equations solver categories